Saving lives through early diagnosis: the promise and role of point of care testing for sickle cell disease. (2nd August 2021) - Dexter, Daniel; McGann, Patrick T.
Abstract: Sickle cell disease (SCD) is a devastating and under‐recognised global child health issue affecting over 300, 000 infants annually, with the highest prevalence in India and sub‐Saharan Africa. Most affected infants born in low‐ and middle‐income countries (LMIC) lack access to SCD testing and die from complications in the first years of life without a formal diagnosis. The majority of deaths are preventable with early diagnosis and provision of inexpensive interventions. Despite global recognition of the urgent need, expansion of SCD newborn screening (NBS) programmes beyond the pilot stage has been obstructed by a dependence on an expensive and logistically challenging centralised laboratory testing model. Recently, several point‐of‐care tests (POCT) for SCD have been developed with promising field validation studies. Here, we summarise the state of POCT for SCD, review barriers and unanswered questions, and discuss optimal strategies for utilising POCT to address the growing global burden of SCD. There is an urgent need to prospectively evaluate the ability of POCT to reduce the morbidity and high early mortality of SCD. To impact a sustainable reduction to this end, it is essential to link a diagnosis with comprehensive SCD care, including wide and affordable access to affordable hydroxycarbamide therapy.